USULAN PERBAIKAN PENGENDALIAN KUALITAS PRODUK DENGAN METODE SIX SIGMA PADA PEMBUATAN LABEL X DI PT. BPP - Tri Widodo (Jurnal Teknik, 2013)
Competition in the corporate world these days of tighter encourage companies to further develop ideas for an effective and efficient in achieving the goals and objectives have been set. Label X is one of the products produced by PT. BPP. For blinding Label X companies also strive to continuously improve product quality by suppressing the number of defects in the production process.Six Sigma is a vision of improved quality to the target 3.4 failures per million opportunities for each transaction of goods and services. So Six Sigma is a method or technique of controlling and improving the quality of which is a dramatic breakthrough in the field of quality management. By using Six Sigma methods can be seen that the quality of label X produced by the company that is pretty good with the 2.79 sigma level of damage to 99.179 million production (DPMO). Implementation of six sigma quality improvement in this study can be concluded that there were three highest causes of product defects: color blur 82%, did not register 9% and cutting 9%.